Espectro das alterações neurológicas e oftalmológicas em pacientes portadores de mutações P.ILE127val no gene da transtirretina - Holanda Filha, Joana Gurgel (2020)
Introduction: Familial transthyretin (TTR) amyloidosis is the most common form of hereditary systemic amyloidosis worldwide. In most patients, the peripheral nervous system is the main target, resulting in familial transthyretin amyloidotic polyneuropathy (TTR-FAP), being a progressive sensorimotor and autonomic neuropathy. Leptomeningeal, and mainly ocular, involvement is also common. Objectives: To prospectively study the evolution of neurological, cardiac and ophthalmological deficits in patients with p.Ile127Val mutations from 2 families, from the State of Ceará, Brazil, with a common ancestor. Methods: We conducted a clinical, cardiological, ophthalmological and neurological evaluation in 2 families with p.Ile127Val mutations in the TTR gene from the state of Ceará and seen at the HUWC. Results: We found a total of 7 patients (4 men and 3 women), 6 with confirmed p.Ile127Val mutation and 1 affected, deceased patient, without genetic confirmation. The condition presented as the classic form of PAF-TTR. The initial manifestation was small fiber sensory and autonomic neuropathy (82.1%) and dry eye syndrome (60%). ENMG was normal in half of them. Cardiovascular involvement revealed progressive heart disease leading to death due to arrhythmias and in two younger individuals there was right bundle branch block. Two patients presented with dry eye syndrome and vitreous opacity as the initial condition, One patient developed corneal ulcers, requiring corneal transplantation and irreversible blindness sequel. One patient with neurological disorders developed amyloid deposit in the ganglionic retinal layer. Conclusion: Eye involvement in a TTR-FAP is still no completely understood, being especially important in Brazil due to the Portuguese ancestry. The present findings are the first report of ophthalmological dysfunction due to p.Ile127Val mutations. Those findings are important to be disclosed at the ophthalmological community, to aid in early diagnosis together with neurologists and cardiologists, as well as to minimize early vision impairment.